D1.17 Impact Assessment Report for RP 4 - Leventis, Georgios; Hadjimitsis, Diofantos G. (My University, 2025)
This document serves as the impact assessment report for RP4 (M49-M66) of the EXCELSIOR project. It offers an overview of the project's achievements during this reporting period, outlining a methodology for monitoring the impact of the ERATOSTHENES Centre of Excellence (ERATOSTHENES CoE) and its partners' activities in alignment with predefined targets. The list of Key Performance Indicators (KPIs), initially outlined in D1.12, have been revised based on feedback received during the project review in November 2022, and was implemented within the previous Reporting Period (RP3). Monitoring the impact during RP4 provides insights into the actions required to meet the KPIs in future reporting periods. This impact assessment document fulfils an essential function in scrutinizing the implementation of the work plan while also directing requisite modifications in conjunction with Work Package (WP) and task leaders to guarantee the attainment of the project's strategic objectives. WP1 delineates the foundational framework for Key Performance Indicator (KPI) monitoring and overarching quality assurance processes, whereas WP3 specifies tangible actions that influence all other WPs to realize the designated Impact KPIs. Engagement with WP3 initiatives regarding strategy formulation guarantees that human resources, infrastructure procurement, and the comprehensive work plan are revised to accommodate emergent priorities. The report systematically assesses a range of activities, including proposals, dissemination initiatives, publications, academic contributions, and collaborative networks, in relation to the predefined KPIs, thereby offering valuable insights into their efficacy and impact.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; Impact Assessment